OsWAK112, A Wall-Associated Kinase, Negatively Regulates Salt Stress Responses by Inhibiting Ethylene Production - Lin, Wei; Wang, Yuehua; Liu, Xinye; Shang, Jian-Xiu; Zhao, Liqun (Frontiers in Plant Science, 2021)
The wall-associated kinase (WAK) multigene family plays critical roles in various cellular processes and stress responses in plants. However, whether WAKs are involved in salt tolerance is obscure. Herein, we report the functional characterization of a rice WAK, WAK112, whose expression is suppressed by salt. Overexpression of OsWAK112 in rice and heterologous expression of OsWAK112 in Arabidopsis significantly decreased plant survival under conditions of salt stress, while knocking down the OsWAK112 in rice increased plant survival under salt stress. OsWAK112 is universally expressed in plant and associated with cell wall. Meanwhile, in vitro kinase assays and salt tolerance analyses showed that OsWAK112 possesses kinase activity and that it plays a negative role in the response of plants to salt stress. In addition, OsWAK112 interacts with S-adenosyl-L-methionine synthetase (SAMS) 1/2/3, which catalyzes SAM synthesis from ATP and L-methionine, and promotes OsSAMS1 degradation under salt stress. Furthermore, in OsWAK112-overexpressing plants there is a decreased SAMS content and a decreased ethylene content under salt stress. These results indicate that OsWAK112 negatively regulates plant salt responses by inhibiting ethylene production, possibly via direct binding with OsSAMS1/2/3.